2017
DOI: 10.1021/acs.jpclett.7b01655
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Reactivity Descriptor for the Oxide-Electrolyte Interface in Li-Ion Batteries

Abstract: Understanding electrochemical and chemical reactions at the electrode-electrolyte interface is of fundamental importance for the safety and cycle life of Li-ion batteries. Positive electrode materials such as layered transition metal oxides exhibit different degrees of chemical reactivity with commonly used carbonate-based electrolytes. Here we employed density functional theory methods to compare the energetics of four different chemical reactions between ethylene carbonate (EC) and layered (LiMO) and rocksal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
241
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(255 citation statements)
references
References 74 publications
12
241
2
Order By: Relevance
“…The origin of O loss and the presence of reduced TMs at OCP are strongly correlated to the oxygen reactivity at the interface between the layered oxide and the electrolyte. Indeed, as explained recently via DFT analysis, chemical oxidation of EC is thermodynamically favored on the LiMO 2 layered oxide and it is induced by the O lattice, via a dissociation mechanism that involves a proton transfer and reduction of the interfacial TMs ions ,. This mechanism can start already at OCP but becomes more favorable at a higher degree of delithiation.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The origin of O loss and the presence of reduced TMs at OCP are strongly correlated to the oxygen reactivity at the interface between the layered oxide and the electrolyte. Indeed, as explained recently via DFT analysis, chemical oxidation of EC is thermodynamically favored on the LiMO 2 layered oxide and it is induced by the O lattice, via a dissociation mechanism that involves a proton transfer and reduction of the interfacial TMs ions ,. This mechanism can start already at OCP but becomes more favorable at a higher degree of delithiation.…”
Section: Discussionmentioning
confidence: 83%
“…On the other hand, the oxygen loss from the layered oxide not only has an impact on the surface structure, but can also undermine the stability of the electrolyte. In recent reports, it has been demonstrated that chemical oxidation of the carbonate solvents, such as ethylene and dimethyl carbonate (EC and DMC, respectively), initiated by the oxygen is indeed thermodynamically favorable and such decomposition could be the major reason why high‐potential cells generate gases and have poor capacity retention ,. The oxygen gas is usually detected via differential electrochemical mass spectrometry (DEMS) at a potential of about 4.7 V vs. Li + /Li, accompanied with prominent CO 2 gas evolution .…”
Section: Introductionmentioning
confidence: 99%
“…In O K-edge, the pre-edge corresponds to transition from O core 1s to the unoccupied hybridized band state of O 2p and TM 3d orbitals, indicating the hole states in TMO bonding. [41,46,47] Ni segregation helps in this regard, because the higher fraction of Ni on surface contributes to capacity without coupling to O 2p orbitals, due to the higher electronic energies of Ni 3+/4+ :e g compared to Co 3+/4+ :t 2g & O 2p resonant band. [13,45] Since the oxidation of O 2− (forming mobile peroxo O 1− ) results in serious side reactions due to oxygen loss and high chemical reactivity toward electrolyte, we believe less O 1− generation on surface must be beneficial.…”
Section: Resultsmentioning
confidence: 99%
“…[40] As shown in Figure 5a, only Li diffusions are observed in the bulk phase during 5 ps of simulation time, and there is no evidence for oxygen migration. [16,17] Electronic structure analysis has assigned the underlying mechanism to the penetration of carbonate molecular HOMO to the O 2p band, which integrates with transition metal 3d bands after delithiation and leads to electron transfer between carbonate molecular and electrode materials, thus SEI layer formation. However, Figure 5b indicates that the oxygen migration to Li layer emerges at only 1 ps simulation of the (104) surface.…”
Section: Surface Oxygen Evolution and Phase Transitionmentioning
confidence: 99%